Modeling for solute transport in mobile–immobile soil column experiment. Issue 2 (3rd May 2016) - Sharma, P. K.; Shukla, S. K.; Choudhary, Rahul; Swami, Deepak
Abstract: This paper presents the behavior of solute transport through mobile–immobile (MIM) soil column based on the laboratory study. The study considers that the advective–dispersive transport equation is used for mobile domain, and the solute exchange between two liquid domains is described as the first-order process. A numerical model is developed for the MIM advective–dispersive transport equation including equilibrium sorption and the first-order degradation. Afterward, the numerical model is used to simulate experimental breakthrough curves (BTCs) for transport of chloride and fluoride through heterogeneous soil column using constant, linear, and exponential distance-dependent dispersion models. It is shown that the behavior of concentration profile produced with a constant dispersion model is similar to the distance-dependent dispersion model. It is found that the constant dispersion and the exponential distance-dependent dispersion models simulate experimental BTCs reasonably well as compared to the linear distance-dependent dispersion model. Hence, the exponential distance-dependent dispersion model is a simple and practical approach to describe the solute transport through the MIM porous media.